The Approach of Agrarian Conflict Resolution through Land Redistribution in Sumberklampok Village - JAYA, I Kadek Gelgel Dwi Utama Jaya; Sarjita, Sarjita; Alfons, Alfons (Sekolah Tinggi Pertanahan Nasional, 2024)
Agrarian conflict is a prevalent issue within the land sector. One such conflict in Indonesia occurs in Sumberklampok Village, Gerokgak Subdistrict, Buleleng Regency, Bali Province. This study aims to analyze the chronology of the conflict, the efforts to manage and resolve agrarian disputes, and the process of land redistribution. The research employs a qualitative methodology with a descriptive approach and analysis. Data were collected through observation, interviews, and document reviews. The findings reveal that the conflict stemmed from the community's control over land previously classified under HGU (Right to Cultivate) Certificates No. 1, 2, and 3 in Sumberklampok Village, alongside the Bali Provincial Government's claim over the land classified under HGU Certificates No. 2 and 3. The resolution process was supported by various stakeholders, culminating in the issuance of a Joint Agreement Letter (SKB) that facilitated land redistribution as part of an agrarian reform program. The Joint Agreement Letter (SKB) was followed by the distribution of 1,613 land certificates to the community, serving as legal proof of ownership and providing legal certainty over their land rights.